Enemy of the State : A Killing Room Novel - Swartwood, Robert (Ashland, OR Blackstone Publishing, 2024)
The world believed Daniel Burke was dead. At least, the few people in the government who knew he existed did. Once part of an elite black op team, Burke faked his death so he could avenge his brother. Now that those responsible have been brought to justice, he plans to leave the country and start a new life. But before Burke can even get on the plane, his old team has tracked him down. The CIA believes Daniel Burke is a traitor--an enemy of the state--who must answer for his crimes. But others in government simply want him dead. Knowing he's been set up, Burke is the only one who can track down and expose the real traitor--before it's too late." Provided by Amazon
Keywords: Special Operations (Military Science) -- Fiction; Spy -- Fiction; Central Intelligence Agency -- Fiction